Simultaneous determination of the novel thiosemicarbazone anti-cancer agent, Bp4eT, and its main phase I metabolites in plasma: application to a pilot pharmacokinetic study in rats - Stariat, Ján; Suprunová, Vlasta; Roh, Jaroslav; Šesták, Vít; Eisner, Tomáš; Filipský, Tomáš; Mladěnka, Přemysl; Nobilis, Milan; Šimůnek, Tomáš; Klimeš, Jiří; Kalinowski, Danuta S; Richardson, Des R; et al. (Biomedical chromatography, 2014)
Novel thiosemicarbazone metal chelators are extensively studied anti-cancer agents with marked and selective activity against a wide variety of cancer cells, as well as human tumor xenografts in mice. This study describes the first validated LC-MS/MS method for the simultaneous quantification of 2-benzoylpyridine 4-ethyl-3-thiosemicarbazone (Bp4eT) and its main metabolites (E/Z isomers of the semicarbazone structure, M1-E and M1-Z, and the amidrazone metabolite, M2) in plasma. Separation was achieved using a C18 column with ammonium formate/acetonitrile mixture as the mobile phase. Plasma samples were treated using solid-phase extraction on 96-well plates. This method was validated over the concentration range of 0.18-2.80 μM for Bp4eT, 0.02-0.37 μM for both M1-E and M1-Z, and 0.10-1.60 μM for M2. This methodology was applied to the analysis of samples from in vivo experiments, allowing for the concentration-time profile to be simultaneously assessed for the parent drug and its metabolites. The current study addresses the lack of knowledge regarding the quantitative analysis of thiosemicarbazone anti-cancer drugs and their metabolites in plasma and provides the first pharmacokinetic data on a lead compound of this class.
Keywords: anti-cancer; Chromatography, High Pressure Liquid; thiosemikarbazony; Tandem Mass Spectrometry; Antineoplastic Agents; 2-benzoylpyridine 4-ethyl-3-thiosemicarbazone; krysa rodu Rattus; pharmacokinetics; zvířata; potkani Wistar; pilotní projekty; Pilot Projects; tandemová hmotnostní spektrometrie; Rats, Wistar; Male; LC-MS; protinádorové látky; Rats; Animals; Thiosemicarbazones; mužské pohlaví; Bp4eT; vysokoúčinná kapalinová chromatografie